2014
DOI: 10.1371/journal.pone.0091672
|View full text |Cite
|
Sign up to set email alerts
|

Footprints of Directional Selection in Wild Atlantic Salmon Populations: Evidence for Parasite-Driven Evolution?

Abstract: Mechanisms of host-parasite co-adaptation have long been of interest in evolutionary biology; however, determining the genetic basis of parasite resistance has been challenging. Current advances in genome technologies provide new opportunities for obtaining a genome-scale view of the action of parasite-driven natural selection in wild populations and thus facilitate the search for specific genomic regions underlying inter-population differences in pathogen response. European populations of Atlantic salmon (Sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 133 publications
(171 reference statements)
3
34
0
Order By: Relevance
“…; Zueva et al. ). Experimental evolution, or ‘evolve and sequence’, studies in D. melanogaster suggest that temperature or parasite treatments may induce major allele frequency shifts at hundreds of loci after only a few generations (Orozco‐terWengel et al.…”
Section: Discussionmentioning
confidence: 96%
“…; Zueva et al. ). Experimental evolution, or ‘evolve and sequence’, studies in D. melanogaster suggest that temperature or parasite treatments may induce major allele frequency shifts at hundreds of loci after only a few generations (Orozco‐terWengel et al.…”
Section: Discussionmentioning
confidence: 96%
“…References to less recent studies can be found in several review papers (Hemmer‐Hansen et al , ; Pujolar et al , , ; Ulrik et al , ; Willette et al , ; Gaither et al , ; Guo et al , ; Elmer, ; Picq et al , , as well as references in the next section as examples of the most recent studies). In contrast, fewer fish studies have used a landscape genomic framework to detecting selection by finding statistical associations between local allele frequencies and environmental variables and those have mainly been performed on salmonids (Zueva et al , ; Hecht et al , ; Hand et al , ). For instance, Hecht et al () used RADseq to genotype nearly 2000 Chinook salmon Oncorhynchus tshawytscha (Walbaum 1792) from 46 localities at about 20 000 SNPs in order to document environmental adaptation throughout the North American range of the species, from California to Alaska.…”
Section: Modern Approaches To Study Genomics Of Local Adaptationmentioning
confidence: 87%
“…; Zueva et al . ). Additionally, salmon express a single copy of the MHC class I and MHC class II, simplifying analysis compared with other species that have many copies (Lukacs et al .…”
Section: Introductionmentioning
confidence: 97%